Effect of NLRP3 inflammasome induced astrocyte phenotype alteration in morphine tolerance - Yuan, Zhenyu; Lu, Boxuan; Zhang, Meiling; Lu, Yinxiao; Wang, Zhihui; Zhang, Wenhao; Cheng, Hao; Wu, Zhifang; Ji, Qing (Frontiers in Pharmacology, 2024)
Morphine is a commonly prescribed analgesic, but its prolonged use is frequently hindered by the development of tolerance. The NLRP3 inflammasome and reactive astrocytes play pivotal roles in the development of morphine tolerance. Reactive astrocytes can be categorized into A1 neurotoxic reactive astrocytes and A2 neuroprotective reactive astrocytes. This study delves into the involvement of the NLRP3 inflammasome and alterations in astrocyte phenotype in the progression of morphine tolerance. We established a morphine tolerance model by administering morphine intrathecally for seven consecutive days. To inhibit the activation of the NLRP3 inflammasome, we utilized MCC950, a specific inhibitor of NLRP3.Behavioral tests revealed that seven days of morphine administration led to the development of tolerance, accompanied by increased protein levels of GFAP, IL-18, NLRP3, and C3 (a specific marker for A1 astrocytes) in the spinal cord. Simultaneously, there was a decrease in the protein level of S100A10, a specific marker for A2 astrocytes. The coadministration of morphine and MCC950 not only significantly slowed the development of morphine tolerance but also reversed alterations in the levels of NLRP3, IL-18, GFAP, C3, and S100A10 proteins. In conclusion, our findings highlight a significant association between NLRP3 inflammasome activation and the emergence of morphine tolerance, underscoring its pivotal role in the transformation of astrocytes into the A1 phenotype. Moreover, suppressing the NLRP3 inflammasome has the potential to revert the changes in astrocyte phenotype, thereby mitigating the development of morphine tolerance.